Kepuasan komunikasi dan hubungannya dengan komitmen kerja dalam kalangan pekerja sektor awam - Ahmad Marzuki, Najib; Omar@Aziz, Umi Zunianti Nurbaya (Universiti Utara Malaysia, 2009)
Communication satisfaction and work commitment are two important elements for workers in an organization.This study was aimed at identifying the relationship bet ween dimensions of communication satisfaction (seven dimensions) and organizational commitment in a public organization; and differences in work commitment based on age, gender and marital status.A total of 169 respondents from a public organization were chosen through simple random sampling. Communication satisfaction was measured using the Communication Satisfaction Questionnaire (CSQ) by Down and Hazen (1977) while work commitment was measured using Organizational Commitment Scale by Allen and Meyer (1996). Results indicated that there were significant relationships in four dimensions of communication satisfaction (corporate perspective,corporate information, organizational integration and horizontal communication).Communication satisfaction towards superiors, subordinates and feedback were found to be unrelated to work commitment. Differences were also found in work commitment based on age and marital status but not for gender.